(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2022)
An ethnomedicinal plant species survey of the Vijayapur district of Karnataka comprising thirteen talukas was conducted from March 2018 to July 2021. The purpose of this survey was to document the Ethnomedicinal plant species used for animal and insect bites. The present study was initiated with an aim to identify Ethno-medicinal plant species resources from traditional practitioners of the Vijayapur district. There are about 21 plant species of angiosperms belonging to 20 genera and 15 families were found to be used as animal and insect bites.